Motivasi sukarelawan pelancong : sukarelawan Raleigh International - Mohd. Fuza, Zatul Iffah (2008)
This research entails investigation of the Motivational of Volunteer Tourism: Volunteer Raleigh International. Raleigh International expeditions are open to â€œvolunteer tourismâ€?, aged 17 to 25, from the UK and abroad. In this expedition, all volunteers will be contribute to long term environmental activity, community project such as conservation effort, living with community in least developed rural areas whilst installing gravity water feed system. As a registered charity, Raleigh International is dependent on fundraising activities and asks all volunteer to contribute towards the charity work and expenses. The objective of this study is to conduct survey analysis of volunteersâ€™ motivational priorities, to measure volunteersâ€™ satisfaction at the Raleigh International expedition, and to define the impact to the local community cause of volunteer tourism activities. The result indicate that there are five motives priorities of volunteerism from 14 motives that listed in the questionnaire were â€œto contribute something goodâ€? (19.5%), followed by â€œto learn something newâ€? (18.5%), â€œto do something different from ordinary jobâ€? (15.9%), â€œsocializing with communityâ€? (15.2%), and â€œfor funâ€? (9.1%). Investigation on their satisfaction levels show the highest mean of satisfaction are â€œoverall experienceâ€? and â€œtraining / orientationâ€? follow by â€œmanagementâ€™s performanceâ€?, â€œteam performanceâ€? and â€œpersonal accomplishmentâ€?. Research Findings from the local community at Kampung Paus and Kampung Miruru, Ranau Sabah, found that there are only positive impacts from the volunteer Raleigh International activity, which are â€œfacilities improvementâ€?, â€œintroduction of their village to other peopleâ€? and â€œincrease local community income from the Raleigh International activityâ€?. In general, these findings should be able to provide support to government and others organization towards the sustainable tourism development, help to increase the tourist arrival to Malaysia and at the same time reduce the negative impact cause by tourism activity.